Effect of thymol and carvacrol, the major components of thymus capitatus on the growth of pseudomonas aeruginosa - Althunibat, Osama Yousef; Qaralleh, Haitham; Abboud, Muayad; Khleifat, Khaled; Majali, Ibrahim S.; Darnis, Deny Susanti; Aldal'In, Hammad Khalifeh H.; Yassin Ahmed Al-dalin, Sati (Journal of Pure and Applied Microbiology, 2016)
his study was designed to evaluate the antibacterial activity of Thymus capitatus and two of its major components namely thymol and carvacrol. The dried leaves were extracted using soxhlet apparatus. Thymol and carvacrol were isolated using normal phase column chromatography. The antibacterial activity of the leaves extract, thymol and carvacrol were estimated using agar disc diffusion and broth dilution methods against four bacterial strains. The leaves extract was found to show a broad spectrum of antibacterial activity against all the tested bacterial strains. Pseudomonas aeruginosa was the most sensitive bacteria. The purified compounds exhibited relatively stronger antibacterial activity than the extract. Thymol fraction exhibited stronger antibacterial activity than carvacrol. Thymol fraction exhibited MIC values ranging from 0.005 – 0.008 mg/mL while carvacrol fraction exhibited MIC values ranging from 0.007 – 0.008 mg/mL.